Evaluation of cast metallic posts reproduction according to its quantity and position inside the casting ring Avaliação da reprodutibilidade dos núcleos metálicos fundidos em função da quantidade e posicionamento dos padrões de resina no anel de fundição - Luciana de Rezende Pinto; Gerson Bonfante; José Fernando Scarelli Lopes (University of São Paulo, 2005)
The aim of this study was the evaluation about the influence of the quantity and the localization of resin patterns to cast metallic posts in its diameter and length reproduction. Seventy-two patterns for posts were fabricated by using prefabricated FKG plastic posts and divided for casting in 3 groups: G1-small ring/4 patterns, G2- medium ring/6 patterns, G3- big ring/8 patterns. Half of the patterns of each group were placed on the right side of the ring midline and the other half, on the left side, in order to guide the ring inside of the centrifuge. Using the comparative microscope, measures of diameter and length in different places were obtained before and after casting. The results were submitted to statistic analysis (ANOVA two way and Tukey's test), to make possible these observations: 1°) the position of patterns didn't influenced the measured dimensions. 2°) the same happened with the quantity of patterns inside the ring. 3°) only the pins of group G3 have presented statistically significant diameter differences. In conclusion, 1°) the position of patterns inside the ring and its quantity did not result in significant changes in pins length and diameter. 2°) Although there were no significant length alterations, significant ones were observed in the diameters 3, 6, and 9mm of Group G3. O objetivo deste trabalho foi avaliar a influência do número e localização de padrões de resina para fundição de núcleos metálicos fundidos (NMF), na reprodução do diâmetro e comprimento dos pinos. Foram confeccionados 72 padrões de resina utilizando pinos plásticos pré-fabricados e divididos para fundição em 3 grupos: G1- anel pequeno/4padrões, G2- anel médio/6 padrões e G3-anel grande/8 padrões. Metade deles foi posicionada à direita da linha média do anel e metade à esquerda, servindo de orientação para posicionar o anel na centrífuga. Através do microscópio comparador foram obtidas medidas antes e depois da fundição, tanto do comprimento quanto do diâmetro em diferentes locais. Os resultados foram submetidos à análise estatística (ANOVA a dois critérios e Tukey), possibilitando as seguintes observações: 1°) a posição dos padrões não exerceu influência nas dimensões mensuradas. 2°) o mesmo ocorreu com a quantidade de padrões dentro do anel. 3°) apenas em relação ao diâmetro (3 e 6mm) dos pinos do grupo G3, houve diferença estatisticamente significante. Conclui-se que: 1°) a posição do padrão dentro do anel e o número de padrões não resultou em alteração significativa do comprimento e diâmetro dos pinos. 2°) A variação de diâmetro (3, 6, e 9mm) foi significante apenas para os pinos do grupo G3.